2021
DOI: 10.1080/13683500.2021.1963216
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 vaccine confidence and tourism at the early stage of a voluntary mass vaccination campaign: a PMT segmentation analysis

Abstract: Restarting the mass tourism industry relies on the success of the COVID-19 vaccination campaign which requires individuals' voluntary participation to reduce health risks to hosts and visitors. This study identifies segments of Italian residents based on vaccine confidence at the early stage of a voluntary mass vaccination programme. Using a survey held with 3893 Italian residents, two COVID-19 vaccine confidence clusters were identified. These clusters were compared and revealed significant differences in res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 45 publications
1
42
0
2
Order By: Relevance
“…Vaccine tourism is the new approach taken by countries like the USA to restart the ill sector and has gained some popularity (Gulati 2021;Higgins-Desbiolles et al 2021). Whatever the cases, an intensive vaccination program is undoubtedly the aspired holy grail to curb the severely impaired tourism sector (Williams et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Vaccine tourism is the new approach taken by countries like the USA to restart the ill sector and has gained some popularity (Gulati 2021;Higgins-Desbiolles et al 2021). Whatever the cases, an intensive vaccination program is undoubtedly the aspired holy grail to curb the severely impaired tourism sector (Williams et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, the increase in the number of pro-vaccine tourists and the fact that these people start to travel more have led to an increase in tourists' intention to travel to a destination and stay in a hotel in general. Williams, Nguyen, Del Chiappa, Fedeli and Wassler (2021), on the other hand, classified tourists into two groups as high-confidence and low-confidence. It has also been suggested that those with high confidence are willing to access the vaccine as quickly as possible and their intention to travel will increase after being vaccinated.…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…Therefore, risk perception and travel intention are seen as fundamental issues in tourism marketing and tourist behaviour studies. In the tourism sector, which has been closed for a long time, studies on vaccination and vaccinated tourists have become essential in the pandemic literature (Adongo et al, 2021;Gursoy et al, 2021;Ma et al, 2021;Schlagenhauf et al, 2021;Williams et al, 2021). In particular, it is necessary to improve studies on the COVID-19 vaccines to reduce the fear and anxiety of travel which increased during the pandemic.…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…Indeed, the global vaccination process is crucial for the reboot of the mass tourism industry. In fact, the voluntary participation of people is required to reduce the health risks of guests, visitors, and staff [85]. However, while immunisation is highly effective for public health, even more efforts are needed to improve currently suboptimal rates of vaccination against various diseases among adults who may be at risk due to their age, medical condition or occupation [86].…”
Section: Long-run Implications and Effect Following Pandemicsmentioning
confidence: 99%